2018
DOI: 10.1371/journal.pone.0193157
|View full text |Cite
|
Sign up to set email alerts
|

Circulating small non-coding RNAs reflect IFN status and B cell hyperactivity in patients with primary Sjögren’s syndrome

Abstract: BackgroundConsidering the important role of miRNAs in the regulation of post–transcriptional expression of target genes, we investigated circulating small non-coding RNAs (snc)RNA levels in patients with primary Sjögren’s syndrome (pSS). In addition we assessed if serum sncRNA levels can be used to differentiate patients with specific disease features.MethodsSerum RNA was isolated from 37 pSS patients as well as 21 patients with incomplete Sjögren’s Syndrome (iSS) and 17 healthy controls (HC) allocated to two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
3
6
0
Order By: Relevance
“…They suggest that cellular miR-150 could be regulated by its release into the extracellular space (43). In addition, similarly to what we observed in MG, different studies demonstrated that miR-150 is decreased in PBMCs from Sjögren Syndrome patients while it is increased in the serum of patients and in inflammatory salivary glands (26, 40, 44).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…They suggest that cellular miR-150 could be regulated by its release into the extracellular space (43). In addition, similarly to what we observed in MG, different studies demonstrated that miR-150 is decreased in PBMCs from Sjögren Syndrome patients while it is increased in the serum of patients and in inflammatory salivary glands (26, 40, 44).…”
Section: Discussionsupporting
confidence: 88%
“…As miR-150 is highly expressed in hyperplastic thymuses, the question is whether the serum increase of miR-150 in MG could be linked to a release from the thymus that would explain the serum decrease after thymectomy (10). Indeed, increased expression of miR-150 is often observed both in the serum and inflammatory organs characterized by ectopic lymphoid infiltrations, such as in Sjögren Syndrome (26, 40) and in lupus nephritis (27, 41). To support this hypothesis, we should observe a higher serum level of miR-150 in MG patients with highly hyperplastic thymus.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that miR-150 could be regulated by its release into the extracellular space (80). Similar to the observations in MG, other studies demonstrate reduced miR-150-5p in PBMCs from patients with Sjogren's syndrome, while levels are still increased in the serum and salivary glands (81,82), in analogy with miR-150-5p in PBMCs versus the thymus in MG.…”
Section: Link Between Elevated Circulating Mirnas In Mg and Disease Psupporting
confidence: 56%
“…Identification of differentially expressed miRNAs was carried out in two independent phases. First, expression of 758 miRNAs was screened in MACS-isolated CD1c-expressing cDC2s from the donors included in the discovery cohort using the OpenArray platform as previously described (24, 25) (discovery phase; Supplementary Figure 1). miRNAs with a poor amplification score (<1.24) were excluded from the analysis and low expressed miRNAs (CT>27) were set at 27.…”
Section: Methodsmentioning
confidence: 99%